1999
DOI: 10.1116/1.590834
|View full text |Cite
|
Sign up to set email alerts
|

Band offsets for ultrathin SiO2 and Si3N4 films on Si(111) and Si(100) from photoemission spectroscopy

Abstract: High resolution soft x-ray photoelectron spectroscopy with synchrotron radiation is used to study the interfaces of SiO 2 /Si(111), SiO 2 /Si(100), Si͑111͒/Si 3 N 4 , and SiO 2 /Si 3 N 4 for device-quality ultrathin gate oxides and nitrides. The thin oxides and nitrides were grown by remote plasma deposition at a temperature of 300°C. Aftergrowth samples were further processed by rapid thermal annealing for 30 s at various temperatures from 700 to 950°C. The Si͑111͒/Si 3 N 4 samples were air exposed and formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 13 publications
7
103
1
Order By: Relevance
“…In particular, we obtained a 4.4 eV valence band offset between silicon and amorphous SiO 2 in accord with the measured value. 49,50 For the interface between silicon and monoclinic HfO 2 , we obtained a valence band offset of 2.9 eV, very close to the measured value of 3.0 eV. 51,52 This level of agreement provides confidence for the quantitative determination of defect levels with respect to the silicon band edges.…”
Section: Band Alignmentssupporting
confidence: 63%
“…In particular, we obtained a 4.4 eV valence band offset between silicon and amorphous SiO 2 in accord with the measured value. 49,50 For the interface between silicon and monoclinic HfO 2 , we obtained a valence band offset of 2.9 eV, very close to the measured value of 3.0 eV. 51,52 This level of agreement provides confidence for the quantitative determination of defect levels with respect to the silicon band edges.…”
Section: Band Alignmentssupporting
confidence: 63%
“…[29][30][31] Previous core photoelectron spectroscopic studies of the Si(111)/SiO 2 interface have shown that Si(I) and Si(III) are more abundant than Si 2+ because disrupting an atomically flat (111) surface through layer-by-layer oxidation will cleave either 1 or 3 Si tetrahedral bonds. 6,14,[32][33][34][35] Two Si bonds will be cleaved only at step edges and etch defects, which are a minor component of Si(111) surfaces prepared in this manner. Additionally, the native oxide that forms on an unpassivated Hor Cl-terminated Si(111) surface covers all available oxidation states of Si, from Si(I) to Si(IV), with the majority of the oxide signal appearing as Si(IV) species.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for the latter system, its origin has been widely discussed on the basis of the final-state effect and charge trapping. [37][38][39][40][41] We calculated the change in the energy difference DE GeO 2 or DE SiO 2 at an elevated RH from that at the lowest RH or in UHV for each sample, which is defined as DE change hereafter. Namely, for both the GeO 2 /Ge and SiO 2 /Si samples…”
Section: B Ap-xps Experimentsmentioning
confidence: 99%